The Vegetable Freshness Monitoring System Using RFID with Oxygen and Carbon Dioxide Sensor. (17th June 2012) - Eom, Ki Hwan; Kim, Min Chul; Lee, SeungJoon; Lee, Chang won
Abstract : This paper proposes an oxygen and carbon dioxide concentration monitoring system for freshness management based on radio frequency identification (RFID). Freshness can be checked by various factors including humidity, temperature, oxygen, and carbon dioxide. This paper focuses on oxygen and carbon dioxide. The concentrations of these two gases are related to freshness and affect the food. We use a sensor for monitoring these gases and combine the sensor with an RFID tag. The RFID system is relatively easy to manage. With this combined system, we estimated the freshness of vegetables.